Ultrarapid and ultrasensitive electrical detection of proteins in a three-dimensional biosensor with high capture efficiency. Issue 21 (12th May 2015) - Kim, Bo-Yeong; Sohn, Il-yung; Lee, Doowon; Han, Gill Sang; Lee, Won-Il; Jung, Hyun Suk; Lee, Nae-Eung
Abstract : A bio-FET using 3D sensing channel structures composed of ZnO nanorods and graphene demonstrates the capability of achieving ultrarapid and ultrasensitive immunodetection. Abstract : The realization of a high-throughput biosensor platform with ultrarapid detection of biomolecular interactions and an ultralow limit of detection in the femtomolar (fM) range or below has been retarded due to sluggish binding kinetics caused by the scarcity of probe molecules on the nanostructures and/or limited mass transport. Here, as a new method for the highly efficient capture of biomolecules at extremely low concentration, we tested a three-dimensional (3D) platform of a bioelectronic field-effect transistor (bio-FET) with vertically aligned and highly dense one-dimensional (1D) ZnO nanorods (NRs) as a sensing surface capped by an ultrathin TiO2 layer for improved electrolytic stability on a chemical-vapor-deposited graphene (Gr) channel. The ultrarapid detection capability with a very fast response time (∼1 min) at the fM level of proteins in the proposed 3D bio-FET is primarily attributed to the fast binding kinetics of the probe–target proteins due to the small diffusion length of the target molecules to reach the sensor surface and the substantial number of probe molecules available on the largely increased surface area of the vertical ZnO NRs. This new 3D electrical biosensor platform can be easily extended to other electrochemical nanobiosensors and has great potential for practical applications in miniaturized biosensor integrated systems.